A. $45.00

B. $25.00

C. $4.50

D. $22.50

Answer:
### What is a bond?

**Ivan's** annual earnings for this bond is** $45.00**

A bond is a **pledge**, made by a borrower to pay a **loan **taken back to the **lender** with an interest.

Ivan's annual interest earning would be :

= $1,000 x 4.5 %

= **$45 per year**

Hence, Ivan's** annual earnings** for this bond is **$45.00**

Learn more about **bonds** here : brainly.com/question/1392006

#SPJ1

Perform each of the following computations using the measured quantities below. a. 917.2 + 45.63 = ___________b. 3.423 x 10^-4 - 6.42 x 10^-3 =_________

F(2)=3x^2-6x+2I need help!!!

Find the value of X.

Multiply. 42.9 × 3.45

Convert 51.7% to a fraction in simplest form and a decimal.

F(2)=3x^2-6x+2I need help!!!

Find the value of X.

Multiply. 42.9 × 3.45

Convert 51.7% to a fraction in simplest form and a decimal.

**Answer:**

= F^2 x^2

**Step-by-step explanation:**

(F(x))^2

**Apply the rule: (a) =a (x) = x**

= (Fx)^2

**Apply exonent rule: (a . b)^n = a^n b^n (Fx)^2 = F^2 x^2**

= F^2 x^2

A = 30% of B = 0.3B

B = 90% of C = 0.9C

A = 0.3(0.9C) = 0.27C = 27% of C

B = 90% of C = 0.9C

A = 0.3(0.9C) = 0.27C = 27% of C

**Answer:**

do better and kick butt ( lol) srry not helpful but just what I thought

**Step-by-step explanation:**

f(x)=-2x^2-7x+6

Find f(−3)

**Answer:**

f(-3) = 9

**Step-by-step explanation:**

Step 1: Define

f(x) = -2x² - 7x + 6

f(-3) = x = -3

Step 2: Substitute and evaluate

f(-3) = -2(-3)² - 7(-3) + 6

f(-3) = -2(9) + 21 + 6

f(-3) = -18 + 21 + 6

f(-3) = 3 + 6

f(-3) = 9

Substituting x = -3 into the **function **f(x) = -2x^2 - 7x + 6, we get f(-3) = -33. Therefore, the value of the function at x = -3 is -33.

To evaluate the **function **f(x)=−2x ^2 −7x+6 at x=−3, substitute −3 for x in the function: f(−3)=−2{(−3) }^2 −7(−3)+6

Now, calculate each part of the expression:

(−3) ^2 is 9 because the square of −3 is 9.

−2 times 9 is −18 because −2⋅9 =−18.

−7 times −3 is 21 because −7⋅−3=21.

Now, plug these values back into the **expression**:

f(−3)=−18−21+6

Finally, add and subtract:

f(−3)=(−18−21)+6=−39+6=−33

So, f(−3)=−33.

The **value **of the function

f(x)=−2x^ 2 −7x+6 at x=−3 is −33.

For more questions on **function **

#SPJ3

**Answer:**

y = 2/5x + 24/5

**Step-by-step explanation:**

y - 4 = 2/5(x - (-2))

y - 4 = 2/5(x +2)

y - 4 = 2/5x + 4/5

y = 2/5x + 4/5 + 4

y = 2/5x + 24/5

**Answer:**

0.3

To round 0.273 to the nearest tenth consider the hundredths’ value of 0.273, which is 7 and equal or more than 5. Therefore, the tenths value of 0.273 increases by 1 to 3.

0.273 rounded to the nearest tenth = 0.3